The use of radio and audiotapes as tools for primary health care education in the area of maternal and child health - Urgoiti, Gabriel Jose (Department of Paediatrics and Child Health, 2017)
In the following chapters, I will discuss the effectiveness of radio and audiotapes as appropriate tools for health communication particularly suited to reaching deprived and isolated communities. I will refer to the striking achievements in radio and audiotape projects by drawing on the experiences of more than sixty radio and cassette projects concerned with primary health care in developing countries. I will present a detailed description of my Argentinean and South African radio experiences, focussing on how the two programmes came into existence, the different stages they have gone through, the problems and constraints encountered as well as their strengths and successes. I will describe the audiotape project I am involved in, and demonstrate how audiotapes can be used alone or in conjunction with radio for primary health education.